Vulnerability and its implications: some comments in the light of the Strasbourg case law concerning asylum seekers - Galka, Katarzyna (2021)
A decade has passed since the European Court of Human Rights (ECtHR/Court) for the first time recognized asylum seekers as ‘a particularly underprivileged and vulnerable population group in need of special protection’ (M.S.S. v. Belgium and Greece, 2011). For many years this approach could be seen as forming a part of the Strasbourg paradigm with regard to the protection of rights and freedoms of foreigners seeking for international protection in States Parties to the European Convention on Human Rights (ECHR). Despite a noticeable shift within this paradigm (see especially Ilias and Ahmed v. Hungary, 2019), vulnerability – although now on more individualized, in contrast to its group form, when the applicant's vulnerability is determined by belonging to a specific category of persons ‒ still have a role to play in the ECtHR’s assessments of responsibility of the respondent States with regard to the violations of the applicant's rights. Recognizing vulnerability as a normative category in the Strasbourg case law, thus as a qualification that produces concrete, legal effects for States’ obligations under the ECHR (which must be seen as a primary, overriding justification for its application by the Court), the present article examines the ECtHR’s references to vulnerability of asylum seekers, explaining the structure of this argument (how and to what extent it is applied, on what grounds), with a special focus on the legal consequences associated to it in the light of the Strasbourg case law.